Modal interactions due to friction in the nonlinear vibration response of the "Harmony" test structure: Experiments and simulations. (18th August 2016) - Claeys, M.; Sinou, J-J.; Lambelin, J-P.; Todeschini, R.
Abstract: The nonlinear vibration response of an assembly with friction joints – named "Harmony" – is studied both experimentally and numerically. The experimental results exhibit a softening effect and an increase of dissipation with excitation level. Modal interactions due to friction are also evidenced. The numerical methodology proposed groups together well-known structural dynamic methods, including finite elements, substructuring, Harmonic Balance and continuation methods. On the one hand, the application of this methodology proves its capacity to treat a complex system where several friction movements occur at the same time. On the other hand, the main contribution of this paper is the experimental and numerical study of evidence of modal interactions due to friction. The simulation methodology succeeds in reproducing complex form of dynamic behavior such as these modal interactions.